Integrated management : how sustainability can create value within any business - Sroufe, Robert (Emerald Publishing Limited, 2018)
An exciting vision of what we can aspire to whensustainability is integrated within strategic practices across enterprisefunctions, systems, supply chains, and cities. The book will enable decision makers to recognize a new era of innovative value creation.